y7(y-4)=3(3+y)-1

Simple and best practice solution for y7(y-4)=3(3+y)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y7(y-4)=3(3+y)-1 equation:



y7(y-4)=3(3+y)-1
We move all terms to the left:
y7(y-4)-(3(3+y)-1)=0
We add all the numbers together, and all the variables
y7(y-4)-(3(y+3)-1)=0
We multiply parentheses
y^8-4y^7-(3(y+3)-1)=0
We calculate terms in parentheses: -(3(y+3)-1), so:
3(y+3)-1
We multiply parentheses
3y+9-1
We add all the numbers together, and all the variables
3y+8
Back to the equation:
-(3y+8)
We do not support eypression: y^8

See similar equations:

| 4(-3h+2)=2(6h-21) | | (7.7x+7.8)+(7.1x+6.3)=129.54 | | 2x+5=8x-5-x | | -5p=-2=-37 | | w−–1=4 | | x5-10=275 | | 2=x/5=12 | | 9y−8y=9 | | n-29=16 | | 3x+57=6x-12 | | 54=8y-2y | | 48=12u-4u | | 4x+1+43=180 | | H(3.25)=4.9t^2+50 | | 5x+4=-32 | | y+1.8=9.78 | | 4(2n-1/4)=7 | | 4(x-8)1/5=16 | | 6x=18;x | | 16x=528 | | 7(-5-7x)=-231 | | 12x-18=18x+10 | | (−x−3)−(5x+2)=0 | | 4x+1=40 | | 5/3(x-5)=30 | | -6x-18=-3×+3(6-4x) | | 8y=121.5 | | (4x^2+4x+3)–(x^2+x+1)= | | 2(-9+4x)=-98 | | -65=8(v-8)-3(5+2v) | | 110+4x+x=180 | | 5x+7+46=180 |

Equations solver categories